THE EFFECTIVENESS OF SOCIOLOGICAL STUDIES IN FORMING AN ADAPTIVE SOCIETY IN THE ERA OF GLOBALIZATION - Yusuf, Yusuf (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The COVID-19 pandemic caused social change that occurred so quickly that people started to change their behavior in regard to their daily life. Based on these reasons, this study aims to provide information or identify social changes and impacts in the new normal era caused by the COVID-19 pandemic, to analyze using a sociological perspective, namely through the theory of functionalism put forward by Talcott Parsons. This type of research is descriptive qualitative research using library research data collection techniques with various references from books, previous studies that can provide an overview of behavior before and after the COVID-19 pandemic, and information from various media credible mainstream masses. Social change in society in the new normal era is an issue of the social system, which is currently hot to suppress the coronavirus and its effects. Parsons has long provided the key to the success of achieving a new social system, namely through AGIL. New Normal can be achieved well if it has gone through various considerations of various mature indicators with good collaboration between community components. Keywords: New Normal; Social Change; Talcott Parsons